Effects of Laboratory Activities through the Argumentation Based Inquiry Approach on 7th Grade Students' Conceptual Learning Electricity in Our Daily Life Unit - (:unkn) unknown (PAMUKKALE UNIV, 2015)
The purpose of this study is to explore the effects of laboratory activities through the Argumentation Based Inquiry (ABI) approach (adopted from the Science Writing Heuristic - SWH approach) on students' conceptual learning levels. ABI approach which is an inquiry based approach was constructed Keys, Hand, Prain and Collins (1999). In the study, quasi experimental design with pretest and posttest control group was used. The experimental group performed laboratory activities through ABI approach, the control group performed laboratory activities through traditional approach. The sampling of our study was comprised of the students from a primary public school in Yalova. The students were 7th graders in the academic year 2010-2011. A total of 65 students participated in our study. The experimental group (N=33) and the control group (N=32) were determined randomly. Conceptual Test, a two-tier multiple choice test, was used in this study as the instrument. There are 15 two-tier test items in the Conceptual Test. After the implementation there was a significant difference between the experimental and the control groups in favor of the experimental group in terms of concept learning level.
Keywords: Inquiry; Argumentation Based Inquiry Approach; Conceptual Learning